The Effect Of The Cooperative Script Learning Model On The Critical Thinking Abilities Of Grade XI Economics Students At SMAN 1 - Rawatul Afna; Mira Chairani; Mauliana Wayudi (STMIK Indonesia Banda Aceh, 2026)
Critical thinking ability is an intellectual process of seeking, analyzing, and evaluating information from observations or experiences, then using it to act and formulate a conclusion. The low critical thinking ability of students is an educational problem; One effort to improve critical thinking ability is by choosing the right learning model. This research aims to determine the effect of the Cooperative Script learning model on students' critical thinking skills in 11th-grade Economics at SMAN 1 Samalanga. The research method used was quasi-experimental with a nonequivalent control group design. The sample consisted of two classes: an experimental class using the Cooperative Script model and a control class using conventional teaching methods. The research instrument included pretest and posttest questions to measure students' critical thinking skills. The results showed a significant difference between the posttest scores of the experimental and control classes. Students in the experimental class demonstrated higher improvement in critical thinking skills compared to those in the control class. Thus, the Cooperative Script learning model is proven effective in enhancing students' critical thinking skills in Economics subjects.